The complete chloroplast genome and phylogenetic analysis of Sida szechuensis matsuda (Malvaceae). Issue 11 (2nd November 2021) - Guo, Dong-Qin; Li, Hai-Ling; Liu, Chang; Zhang, Hua; Du, Hui-Hui; Zhou, Nong
Abstract: Sida szechuensis Matsuda is an economically and medicinally important plant. Here, we report the first chloroplast (cp) genome of the genus Sida ( S. szechuensis ). The complete cp genome is 159, 878 bp in length with an overall GC content of 36.9% and consists of a large single copy region (LSC, 89, 426 bp), a small single copy region (SSC, 114, 715 bp), and a pair of inverted repeat regions (IRa and IRb, 25, 288 bp). The genome encodes 111 unique genes, including 78 protein-coding genes, 29 tRNA genes, 4 rRNA genes, and 1 pseudogene. Phylogenetic analysis constructed using the maximum likelihood (ML) method showed that Sida was closely related to Malvastrum and Malva .